Estimating the Smoothing Parameter in the So-Called Hodrick-Prescott Filter - Ekkehart Schlicht (Institute for the Study of Labor (IZA), 2004)
This note gives a fairly complete statistical description of the Hodrick-Prescott Filter (1997) which has been proposed in the context of my seasonal adjustment method (Schlicht 1981, 1984). A statistics estimator for the smoothing parameter is proposed that is asymptotically equivalent to the maximum-likelihood estimator and has a straightforward intuitive interpretation. The method is illustrated by an application and several simulations.
Keywords: C22; 330; Hodrick-Prescott filter; Kalman filtering; Kalman-Bucy; state-space models; random walk; time-varying coefficients; adaptive estimation; Zeitreihenanalyse; Saisonbereinigung; Zustandsraummodell; Schätztheorie; Theorie